DEMOCRACY THREAT TOWARDS SECURITY PROTECTION ON THE ELECTION - Juniar Laraswanda Umagapi (Paradigma POLISTAAT: Jurnal Ilmu Sosial dan Ilmu Politik, 2026)
Indonesia is a country full of diversity, home to numerous different ethnic groups, languages, and religions. Many factors can be the main threat of the conflict in Indonesia. In this paper, it would focus on the tribe, religion, race, and intergroup (SARA) issue in Politics. This year Indonesia holds the first simultaneous election, which creates a lot of dynamics conflict in Indonesia. People fight with each other because of their choice of the candidates in the President or even in the legislative election. A lot of issues occur such as hoax issues in the election, dynasty politics, money politics, illegal campaigns and etc. The difference of the political choice creates a religious conflict, even the discord among families. The combination of the president and legislative election in one day creates a conflict. Then the big question appears, is democracy a cause of peace? Though peace causes democracy, democracy does not cause peace. Based on perpetual peace by Immanuel Kant in 1795, most people will not choose a war except for protection for their life because they are the one who got the negative impact of war, but in a democratic country like Indonesia, freedom of speech everywhere, we can choose where we belong and cultural diversity exists, that is more likely as a factor of conflict especially in politics era right now. Democracy is when people do not live in fear anymore. This research concludes that even though Indonesian always creates a conflict especially after the election but we still called as a process of democracy so it means democracy is when people can express themselves self-confidently without feeling guilty, but the consequence of democracy is conflict everywhere.